REVOLUTIONIZING MARKETING MANAGE REVOLUTIONIZING MARKETING MANAGEMENT MENGHUBUNGKAN CELAH DIGITAL MARKETING MELALUI PELATIHAN DAN OTOMATISASI P L U T KEBUMEN - Wisda Gunawan, Mengga Kusuma; Rakhmat Susanto; Lusiyanto; Dwi Rizki Saputra; Surya Adi Cahyana (Jurnal Inovasi Pengabdian Masyarakat, 2024)
In the context of Micro, Small, and Medium Enterprises (MSMEs), a revolution in marketing management plays a crucial role in enhancing competitiveness and business sustainability. This article discusses an innovative approach that bridges the gaps in digital marketing for MSMEs through a combination of training and automation strategies. Firstly, training serves as the foundational element to empower MSME owners and their marketing teams with the essential digital skills. The training encompasses understanding digital platforms, social media, and data analytics, while also imparting marketing strategies tailored to the size and resources of MSMEs. Subsequently, automation emerges as an effective solution to overcome the resource constraints often faced by MSMEs. Leveraging simple and affordable automation tools can assist in managing marketing campaigns, inventory, and enhancing customer interactions without requiring substantial investments. By integrating training and automation, MSMEs can optimize the use of digital technology in their marketing efforts. This not only improves visibility and market access but also enhances operational efficiency and the ability of MSMEs to compete with larger market players. This approach can unlock new opportunities, increase market share, and have a positive impact on the growth and sustainability of MSMEs in an increasingly digital business ecosystem.